2014
DOI: 10.5812/numonthly.22112
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional Cardiovascular Biomarkers and Estimation of Cardiovascular Risk in Predialysis Chronic Kidney Disease Patients and Their Correlations With Carotid Intima Media Thickness

Abstract: Background:Cardiovascular biomarkers such as N-terminal pro-B-type natriuretic peptide (NT-proBNP), cardiac troponin T (cTnT), hs-CRP (high sensitivity C-reactive protein), and albuminuria predict underlying heart disease in the general population as well as CKD patients.Objectives:We aimed to study the association of NT-proBNP, cTnT, hs-CRP, and spot urine albumin creatinine ratio with carotid intima media thickness (CIMT) for cardiovascular risk estimation in predialysis CKD (chronic kidney disease) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…However, only the CKD-EPIcr equation showed significant association with insulin. In contrast we found no association between CKD and arterial stiffness, which is consistent with previous reports 30. Overall both equations showed significant associations with most of the major vascular risk markers.…”
Section: Discussionsupporting
confidence: 92%
“…However, only the CKD-EPIcr equation showed significant association with insulin. In contrast we found no association between CKD and arterial stiffness, which is consistent with previous reports 30. Overall both equations showed significant associations with most of the major vascular risk markers.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes mellitus, chronic glomerulonephritis and hypertension were the major aetiology of renal disease, accounting for 30(37.5%), 24 (Table 3). On multiple linear regression analysis, the significant predictors of elevated serum CRP in the CKD patients were low eGFR (p = 0.03) and high BMI (p = 0.03) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Its level correlates with carotid intima media thickness in CKD patients, hence can serve as a biomarker to estimate cardiovascular risk. 24 C-reactive protein has also been implicated as an actual promoter of atherosclerotic disease progression by binding to LDL, facilitating its deposition on the arterial wall and activating the complement system. 25,26 The median serum level of hsCRP was significantly higher in the CKD group compared to the controls who did not have CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line of reasoning, Günal et al (2006) showed a decrease in cIMT with an strict volume control in HD patients, a fact that has not been proven to be true in PD patients (Hiramatsu et al, 2007). As a last hypothesis for the increased cIMT in HD patients, there is the possibility that the previously described increased levels of pro-BNP in HD patients (Nakatani et al, 2002; Al-Hweish et al, 2010; Sanjuan et al, 2011) could favor an increased cIMT, as it has been published for CKD patients (DeFilippi et al, 2005; Sathi et al, 2014); a similar effect has been described for Troponins (Al-Hweish et al, 2010; Caliskan et al, 2012).…”
Section: Discussionmentioning
confidence: 63%